Penerapan Lembar Kerja Analisis Kesalahan Berbasis PBL terhadap Pemahaman Surat Resmi dan Sikap Kritis Murid Kelas VI - Aurellia, Anindya Gilta; Purwati, Panca Dewi (YASIN, 2025)
Elementary school pupils’ understanding of official letters and the development of critical attitudes remain challenging in Bahasa Indonesia instruction, while studies that specifically integrate Lembar Kerja Analisis Kesalahan (Error Analysis Worksheet) with the Problem-Based Learning (PBL) model are still limited. This study aimed to describe the implementation of a PBL-based Error Analysis Worksheet and to evaluate its effectiveness in improving sixth-grade students’ understanding of official letters and their critical attitudes. A mixed-methods approach with an embedded concurrent design was employed, involving 14 students selected through purposive sampling. Data were collected through pretest–posttest assessments, classroom observations, interviews, and document analysis of students’ Error Analysis Worksheets (LKAK), and were analyzed using descriptive statistics, N-gain testing, and Miles and Huberman’s qualitative analysis model. The results show an increase in the mean score from 66 to 86, an improvement in learning mastery from 57.14% to 92.86%, and an N-gain value of 0.60, which falls within the medium category and is interpreted as fairly effective. Qualitative findings further reveal that most students demonstrated critical attitudes in the “very good” category, as indicated by their ability to maintain focus, consistently identify errors, and revise their work independently. These findings enrich the development of constructivist theory and the literature on Bahasa Indonesia learning, particularly regarding the integration of error analysis within problem-based instruction. The study concludes that a PBL-based Error Analysis Worksheet is an effective instructional strategy for enhancing students’ understanding of formal texts and their critical reasoning, implying the need for teachers to optimize the use of this tool and opening opportunities for its broader application to other Bahasa Indonesia materials and more diverse school contexts.